Utilization of Learning Design at the Educational Communication Information Technology Center (BTIKP) to Support the Availability of School Learning Devices in Gorontalo City - Frezy Paputungan; Rahmat Olii (Jurnal Ilmu Pendidikan dan Budaya, 2023)
The development of ICT in education means that in the 21st century there has been a revolution in learning resources which mandates that the role of the teacher is no longer the only source of learning and the classroom is no longer the only place of learning. The virtual world with Google, Wikipedia and Kindle is also a place for learning without being limited by space and time. Therefore, teachers' external challenges in learning will become increasingly complex. To support a learning process that keeps up with current developments, the Educational Information and Communication Technology Center (BTIKP) is usually under the auspices of the Provincial Education Service in a region. This center is really needed to support the creation of tools, methods, models, resources and learning media in schools. Especially in Gorontalo Province, BTIKP has not yet been formed. So the demands and needs of school education are still very minimal, let alone the availability of appropriate learning devices. To answer this problem, research is needed that proves that BTIKP is important to be formed to support the learning process in Gorontalo City schools.